Seychelles : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report ;, 2020)
This paper refers to Seychelles' Request for Purchase Under the Rapid Financing Instrument (RFI). The near-term economic fallout of the coronavirus disease 2019 pandemic is expected to be severe. Restriction in travel will hinder tourism and weaken fiscal and external positions, creating large additional financing needs. The authorities reacted swiftly by taking immediate measures of containment, including border closures, strengthening health policy responses and supporting households and firms. The emergency IMF support under the RFI provides timely resources to the authorities to address the urgent balance of payments and budgetary needs. The assistance of other international financial institutions and development partners is crucial to close the remaining financing gaps, ease the adjustment burden, and preserve economic growth. The authorities are committed to transparency and good governance in the use of emergency financing by providing monthly reports of pandemic-related expenditure to the National Assembly and undertaking an independent audit of such spending and procurement and publishing the results.